Analisis Rasio Keuangan Untuk Memprediksi Kondisi Financial Distress (Studi Empiris Pada Perusahaan Property dan Real Estate yang Terdaftar Di BEI Tahun 2018-2020) - Zulma, Gandy Wahyu Maulana; Wahyudi, Ilham; Sutyowati, Sutyowati (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to compare which financial distress analysis model is the best and provide evidence of whether financial ratios have an effect on predicting financial distress conditions in companies. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange from 2018 to 2020. The sampling method used is purposive sampling. The sample used in this study was 35 companies with an observation period of 3 years with sampling criteria. The type of data used is secondary data. The analytical method used in this research is logistic regression analysis with statistical techniques and descriptive analysis. The results of this study indicate that (1) Return On Equity (ROE) has a significant effect in predicting financial distress conditions; (2) Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Current Liabilities to Total Asset Ratio (CLAR), and Return On Assets (ROA) have no significant effect in predicting financial distress. ; (3) Grover Method is the most significant method to be used in predicting financial distress conditions in property and real estate companies listed on the Indonesia Stock Exchange in 2018-2020.